Meta4CBC: Metamodel for Competency-Based Curriculum Design in Higher Education - Ania Cravero; Dante Álvarez; Samuel Sepúlveda; Maria-Isabel Valdivieso; Lilia Muñoz (Applied Sciences, 2024)
Meta4CBC is proposed as an innovative metamodel for competency-based curriculum design in higher education, addressing the critical need to adapt curricula to contemporary challenges driven by globalization, technological advancement, and climate change. Inspired by the Business Motivation Model and Semantics of Business Vocabulary and Business Rules metamodels, Meta4CBC seeks to overcome the limitations of current CBCD models by providing a coherent structure that integrates curriculum components at supra, macro, meso, micro, and nano levels and establishes a common language that facilitates interdisciplinary collaboration. The proposal promotes curriculum alignment and coherence while supporting the development of software tools to assist in curriculum design, automate repetitive tasks, and provide data analysis for informed decision-making. The validation of Meta4CBC was conducted through a multi-step methodology involving proof of concept, expert judgment, and practical application. After defining the components through a systematic literature review, the metamodel was tested in the Computer Engineering program at the University of La Frontera. This testing verified its adaptability and alignment across curriculum levels. Experts from various Chilean universities reviewed the model, providing feedback for refinement.